Echocardiographic and ambulatory electrocardiographic findings in elite water-polo athletes - Zakynthinos, E.; Vassilakopoulos, T.; Mavrommati, I.; Filippatos, G.; Roussos, C.; Zakynthinos, S. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The aim of this study was to investigate the echocardiographic and electrocardiographic findings in top water-polo athletes and test the hypothesis that their hearts exhibit dilatation associated with hypertrophy secondary to the mixed type (isotonic and isometric) of exercise they are subjected to. Eighteen athletes of the Greek national water-polo team and 15 healthy sedentary men serving as controls were studied. All underwent an echocardiogram, a standard 12-lead ECG and 24-h ECG monitoring. In athletes, as compared to healthy controls, an increase was detected in the following indices: left ventricular (LV) end-diastolic diameter index (EDDI-LV) (by 10%; P = 0.02), interventricular septal thickness (IVS) (by 32%; P<0.001), thickness of the posterior wall (PW) (by 29%; P<0.001), relative wall thickness (IVS + PW/EDD-LV) (by 12%; P < 0.001) and LV mass index (by 82%; P < 0.001). Mild asymmetric thickening of the septum (IVS/PW = 1.40 and 1.37) was measured in two athletes. LV fractional shortening was normal. Standard 12-lead ECG abnormalities (LV hypertrophy or abnormal repolarization pattern) were observed in 33% of athletes. Athletes had sinus bradycardia during day and night, respiratory arrhythmia (RA) (83% vs 40% of controls; P = 0.03) and sinus pauses (SP) (39% vs 0% of controls; P = 0.02), with occassional arrhythmias and conduction abnormalities. We conclude that top water-polo athletes have dilatation combined with substantial hypertrophy and normal systolic function of the LV In addition they present bradycardia, RA and SP, with occassional arrhythmias and conduction abnormalities.